Cross-sectional research of school principals' view on placement of school nurses in Slovenian schools - Torkar Tanja; Košnik Irena Grmek; Savič Brigita Skela (Sciendo, 2014)
Background: Children spend most of their days in schools, therefore schools play an important role in children's inter-institutional health care.